Mediterraneo - Cederna, Giuseppe 1957-; Bigagli, Claudio 1955-; Abatantuono, Diego 1955-; Conti, Ugo; Bisio, Claudio 1957- (Cecchi Gori Home Video, 2003)
During World War II in the Greek Sea, an Italian ship leaves a handful of soldiers on a little island; their mission is to spot enemy ships and to hold the island in case of attack. The island village seems abandoned and there isn't a single enemy in sight, so the soldiers begin to relax a little.
Original: Italien, 1991
Sottotitoli: in italiano per non udenti
Contenuti speciali: Menù interattivi ed animati
Bildformat 1.85:1
Keywords: Weltkrieg (1939-1945); Feature films; War films; World War, 1939-1945 -- Participation -- Italian -- Drama; World War, 1939-1945 -- Greece -- Drama; Griechenland; Film; DVD-Video